The Effect of Antam's Inflation and Gold Prices on Stock Prices PT. Aneka Tambang Tbk Period Year 2018-2020 - Usu Sumarni; Maman Nurachman; Shofia Annisa R (Journal of Business, Accounting and Finance, 2022)
The study aims to determine the effect of inflation on stock for the period of 2018-2020, to determine the effect of Antam gold prices for the period of 2018-2020. The study population is all reports of inflation, antam gold price and PT. Aneka Tambang Tbk stock price listed on the Indonesia Stock Exchange and the attached webside that has been published. The result of the study is: (1) There is a not have a negative significant between inflation on stock prices (2) There is does not have a negative and significant effect between antam gold price on PT. Aneka Tambang Tbk stock price (3) There is a positive and significant between inflation and antam gold prices on PT. Aneka Tambang stock price